PENGARUH PRODUCT PLACEMENT TERHADAP PURCHASE INTENTION DENGAN BRAND AWARENESS SEBAGAI VARIABEL MEDIASI (STUDI EMPIRIS RESTORAN GOOBNE DALAM DRAMAKOREA “BUSINESS PROPOSAL”) - Rudy Vernando Silalahi; Yuvi Angel (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
There is a phenomenon where someone just knows Goobne after watching the Korean drama "Business Proposal" which will be released in 2022, even though the Goobne restaurant has been in Indonesia since 2018. The purpose of this study was to determine the effect of product placement on purchase intention which is mediated by brand awareness. Data collection was carried out by distributing questionnaires to respondents who had watched the Korean drama "Business Proposal". The sampling technique used is non-probability sampling with purposive sampling method. Data processing is carried out using Partial Least Square (PLS) using SmartPLS software. From the results of the tests that have been carried out, it is found that the product placement and brand awareness variables have a significant and positive influence on purchase intention. The product placement variable has a significant and positive influence on brand awareness. Thus, it is also proven that brand awareness variables can mediate the relationship between product placement variables and purchase intention variables significantly and positively.Bahasa Indonesia Abstrak: Terjadi fenomena dimana seseorang baru mengetahui Goobne setelah menonton drama Korea “Business Proposal” yang rilis pada tahun 2022, padahal restoran Goobne sudah ada di Indonesia sejak tahun 2018. Tujuan penelitian ini adalah untuk mengetahui pengaruh dari product placement terhadap purchase intention yang dimediasi oleh brand awareness. Pengumpulan data dilakukan dengan penyebaran kuesioner kepada responden yang sudah menonton drama Korea “Business Proposal”. Teknik pengampilan sampel yang digunakan adalah non-probability sampling dengan metode purposive sampling. Pengolahan data dilakukan dengan menggunakan Partial Least Square (PLS) yang menggunakan software SmartPLS. Dari hasil pengujian yang telah dilakukan, maka didapatkan bahwa variabel product placement dan brand awareness memiliki pengaruh yang signifikan dan positif terhadap purchase intention. Variabel product placement memiliki pengaruh yang signifikan dan positif terhadap brand awareness. Sehingga, terbukti juga bahwa variabel brand awareness dapat memediasi hubungan antara variabel product placement dan variabel purchase intention secara signifikan dan positif.